Answer:
Equivalent expressions are expressions which are equal. This means they simplify to the same expression. Simplify the two expressions -1.3x - (-8.9x) = 7.6x and -1.3 + (-8.9X) = -10.2x.
Then simplify each option to determine if it is equal -1.3x - (-8.9x), -1.3 + (-8.9X) or neither:
−1.3x−8.9x = -10.2x. This is equivalent to -1.3 + (-8.9X) .
8.9x+(−1.3x) = 7.6x This is equivalent to -1.3x - (-8.9x) .
−8.9x+(−1.3x) = -10.2x This is equivalent to -1.3 + (-8.9X) .
8.9x−(−1.3x) = 10.2x Neither
−1.3x+8.9x = 7.6x This is equivalent to -1.3x - (-8.9x) .
−8.9x+1.3x = -7.6x Neither
Step-by-step explanation:
You can solve this analytically to get
.. 55000*(1 +x/100)^10 = 108193
.. (1 +x/100)^10 = 108193/55000
.. 1 +x/100 = (108193/55000)^(1/10)
.. x = 100*((108193/55000)^(1/10) -1) ≈ 7.00
but I find it just as fast to have a graphing calculator do it.
The city's population is increasing 7% per year.
Answer:
P=1
Step-by-step explanation:
1-6=-5
Answer: the sand in the new terrarium is 2 inches deep.
Step-by-step explanation:
Zach has a terrarium with the dimensions of 20 by 8 and the terrarium was filled with 3 inches of sand. It means that the volume of sand that this terrarium contains is
20 × 8 × 3 = 480 inches³
Zach gets a new terrarium that is larger with the dimensions of 10 by 24. If Zach moved the existing sand in the new terrarium and the height of the sand is represented by h, then the volume of sand into he new terrarium is
10 × 24 × h = 240h
Since the volume of sand in both terrariums is equal, then
240h = 480
h = 480/240
h = 2 inches